Transcriptional repression of the E2-containing promoters EIIaE, c-myc, and RB1 by the product of the RB1 gene. - Hamel, P A (1992)
The protein product of the retinoblastoma susceptibility gene, p110RB1, is a nuclear phosphoprotein [W.H. Lee, J.Y. Shew, F.D. Hong, T.W. Sery, L.A. Donoso, L.J. Young, R. Bookstein, and E.Y. Lee, Nature (London) 329:642-645, 1987] with properties of a cell cycle regulator (K. Buchkovich, L.A. Duffy, and E. Harlow, Cell 58:1097-1105, 1989; P.L. Chen, P. Scully, J.Y. Shew, J.Y. Wang, and W.H. Lee, Cell 58:1193-1198, 1989; J.A. DeCaprio, J.W. Ludlow, D. Lynch, Y. Furukawa, J. Griffin, H. Piwnica-Worms, C.M. Huang, and D.M. Livingston, Cell 58:1085-1095, 1989; and K. Mihara, X.R. Cao, A. Yen, S. Chandler, B. Driscoll, A.L. Murphree, A. TAng, and Y.K. Fung, Science 246:1300-1303, 1989). Although the mechanism of action of p110RB1 remains unknown, several lines of evidence suggest that it plays a role in the regulation of transcription. We now show that overexpression of p110RB1 causes repression of the adenovirus early promoter EIIaE and the promoters of two cellular genes, c-myc and RB1, both of which contain E2F-binding motifs. Mutation of the E2 element in the c-myc promoter abolishes p110RB1 repression. We also demonstrate that a p110RB1 mutant, which is refractory to cell cycle phosphorylation but intact in E1a/large T antigen-binding properties, represses EIIaE with 50- to 80-fold greater efficiency than wild-type p110RB1. These data provide evidence that hypophosphorylated p110RB1 actively represses expression of genes with promoters containing the E2F-binding motif (E2 element).